CYBER LAW DI INDONESIA: TANTANGAN DAN EFEKTIVITAS PENEGAKAN HUKUM TERHADAP KEJAHATAN SIBER - Yaya Mulyajaya (Institute for Research and Community Service (LPPM), Universitas Dharma Indonesia (UNDHI), 2026)
The rapid advancement of information technology has driven the emergence of various innovations in society. In addition to providing significant benefits, these developments have also given rise to various forms of cybercrime, including hacking, personal data theft, electronic fraud, malware distribution, and attacks on electronic systems. Cyber Law serves as a legal instrument that regulates activities in cyberspace while ensuring legal certainty for the public. Indonesia has enacted several legal regulations, including Law Number 11 of 2008 concerning Electronic Information and Transactions, as most recently amended by Law Number 1 of 2024, as well as Law Number 27 of 2022 concerning Personal Data Protection. This study employs a normative legal research method using statutory, conceptual, and comparative approaches